Sinonasal Meningioma in a Siberian Tiger (Panthera tigris altaica) - Louise van der Weyden; Peter Caldwell; Christine Steyrer; Nicolize O’Dell; Alischa Henning (Veterinary Sciences, 2022)
Meningiomas are the most common primary brain tumour in dogs and cats. However, whilst there are numerous reports of extracranial (spinal, orbital and sinonasal) meningiomas in the dog, there have only been a few case reports of spinal meningiomas, and no post-mortem confirmed orbital or sinonasal meningiomas in cats. In this report, a 20-year-old captive tiger (Panthera tigris altaica) with a history of chronic ocular inflammation resulting in enucleation, spontaneously developed tetanic convulsions (epileptic seizures) that over a 2-year period resulted in a gradually worsening condition and the animal was eventually euthanized. At autopsy, a focal, expansile, neoplastic mass was found in the caudal nasal cavity midline, abutting the cribriform plate and slightly compressing the calvarium. Histological analysis revealed nasal turbinates attached to a well-circumscribed expansile multi-lobular mass consisting of interlacing whorls and streams of neoplastic cells supported by a variably fibrous to microcystic collagenous matrix displaying rare psammoma bodies. The diagnosis was sinonasal transitional meningioma. This is the first report of a captive wild felid with an extracranial meningioma, specifically a tiger with a sinonasal transitional meningioma.